Enhancement of interleukin-2 (IL-2) production by 6 different cytokines: heterogeneity among IL-2 producing T cell clones - Holán, V; Minowada, J (Folia biologica, 1993)
The production of interleukin-2 (IL-2) by phytohemagglutinin (PHA)-stimulated human leukemia T cell lines was significantly increased by 6 different cytokines. The most effective cytokines were interleukin-1 alpha (IL-1 alpha) and IL-1 beta; less effective were interferon-alpha (IFN-alpha), tumor necrosis factor-alpha (TNF-alpha), IFN-beta and TNF-beta. The combinations of two cytokines had synergistic or additive effects and increased IL-2 production to a greater extent than either cytokine alone. Other cytokines tested, such as IL-3, IL-4, IL-6, IL-7, IL-8 and IFN-gamma, had no effect on IL-2 production. However, a remarkable heterogeneity in sensitivity to the enhancing effects of the active cytokines was found among the IL-2-producing T cell lines studied. While IL-2 production in the most sensitive cell line, MOLT-16, was increased by all 6 active cytokines, other cell lines responded by increasing IL-2 production to stimulation with only some of the cytokines tested. The production of IL-2 in T cell line H9 was not enhanced by any of the cytokines used. These results show that several cytokines can increase IL-2 production by having a direct effect on the activated IL-2-producing T cells, but also that the outcome of the regulatory effects of individual cytokines depends considerably upon the individual IL-2-producing T cell clone.
Keywords: Interleukin-2; T-Lymphocytes; cytokiny; rekombinantní proteiny; T-lymfocyty; Leukemia, T-Cell; Drug Synergism; Cytokines; Tumor Cells, Cultured; fytohemaglutininy; interleukin-2; Phytohemagglutinins; aktivace lymfocytů; synergismus léků; Humans; Lymphocyte Activation; nádorové buňky kultivované; leukemie T-buněčná; lidé; Recombinant Proteins